Clinical and Genetic Features in Patients With Reflex Bathing Epilepsy. (10th August 2021) - Accogli, Andrea; Wiegand, Gert; Scala, Marcello; Cerminara, Caterina; Iacomino, Michele; Riva, Antonella; Carlini, Barbara; Camerota, Letizia; Belcastro, Vincenzo; Prontera, Paolo; Fernández-Jaén, Alberto; Bebek, Nerses; et al.
Abstract : Objective: To describe the clinical and genetic findings in a cohort of individuals with bathing epilepsy, a rare form of reflex epilepsy. Methods: We investigated by Sanger and targeted resequencing the SYN1 gene in 12 individuals from 10 different families presenting with seizures triggered primarily by bathing or showering. An additional 12 individuals with hot-water epilepsy were also screened. Results: In all families with bathing epilepsy, we identified 8 distinct pathogenic or likely pathogenic variants and 2 variants of unknown significance in SYN1, 9 of which are novel. Conversely, none of the individuals with hot-water epilepsy displayed SYN1 variants. In mutated individuals, seizures were typically triggered by showering or bathing regardless of the water temperature. Additional triggers included fingernail clipping, haircutting, or watching someone take a shower. Unprovoked seizures and a variable degree of developmental delay were also common. Conclusion: Bathing epilepsy is genetically distinct reflex epilepsy caused mainly by SYN1 mutations.